Syntactical Error Analysis on Fieldwork Report Made by the Vocational High School Students - Dwi Atmoko; Fiqih Kartika Murti; Agung Tyas Subekti (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
The study aimed to describe syntactical error on fieldwork report made by the students of SMK Semesta Bumiayu. It was descriptive qualitative research. The data were fieldwork report arranged by the students of SMK Semesta Bumiayu as many as 38 documents. Those were taken by reading and note-taking techniques, validated by content validation, and analyzed by agih method. The result showed that there were 97 syntactical errors coming from the fieldwork report like (1) inappropriate preposition of 7.21%, (2) redudancy of 13.40%, (3) double plural of 15.46%, (4) superlative form of 9.30%, (5) polysyndeton of 24.74%, (6) asyndeton of 11.34%, (7) foreign terms of 18.55%.